2014
DOI: 10.1302/0301-620x.96b4.33249
|View full text |Cite
|
Sign up to set email alerts
|

Short segment pedicle screw instrumentation with an index level screw and cantilevered hyperlordotic reduction in the treatment of type-A fractures of the thoracolumbar spine

Abstract: The purpose of this study was to evaluate and compare the effect of short segment pedicle screw instrumentation and an intermediate screw (SSPI+IS) on the radiological outcome of type A thoracolumbar fractures, as judged by the load-sharing classification, percentage canal area reduction and remodelling. We retrospectively evaluated 39 patients who had undergone hyperlordotic SSPI+IS for an AO-Magerl Type-A thoracolumbar fracture. Their mean age was 35.1 (16 to 60) and the mean follow-up was 22.9 months (12 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…It had been shown in various long term studies that fusion is not necessary to maintain the correction in kyphotic deformity in these fractures even in short segment fi xation 23 . Improvement in clinical outcomes was observed in all patients, and two cases of implant failure were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been shown in various long term studies that fusion is not necessary to maintain the correction in kyphotic deformity in these fractures even in short segment fi xation 23 . Improvement in clinical outcomes was observed in all patients, and two cases of implant failure were found.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have concluded that an LSC six or less is likely to be good candidates, while an LSC seven or more requires the anterior approach to reconstruct the anterior column 14 . However, the signifi cance of LSC has been questioned in thoracolumbar fractures as many studies have shown to have excellent results with posterior only fi xation with intermediate screws at fracture site in patients with LSC score more than seven 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a persistent re-creation of the anatomic alignment might have positive impact on the clinical outcome, particularly in the long-term. Possible solutions to reduce the amount of reduction loss might be the additional implementation of fracture screws that increase stability or additional posterior fusion [23].…”
Section: Discussionmentioning
confidence: 99%
“…Short-segment posterior fixation with pedicle fixation at the level of the fracture (short same-segment fixation) suggests biomechanical advantages toward maintenance of kyphosis correction and reducing failure rates [8]. The trans-pedicular short same-segment construct represents an attempt to rebuild the anterior column without the need for anterior strut graft or plate fixation, hence, avoiding extensive arthrodesis of the motion segments and limited surgery-related injury [9].…”
Section: Introductionmentioning
confidence: 99%